IDENTIFIKASI DAN RESISTENSI BAKTERI Methicillin resistant Staphylococcus aureus (MRSA) DARI ULKUS DIABETIKUM DERAJAT I DAN II WAGNER DI BAGIAN PENYAKIT DALAM RSUD ARIFIN ACHMAD - Meta, Definov Tacsa; Endriani, Rita; Sembiring, Ligat Pribadi (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Diabetic ulcers is a chronic complications of diabetic mellitus which caused people treated in hospital about 80%. Patients with diabetic ulcers need more care and additional costs. It will be wretched if the infection caused by multidrugs resistant bacterials like Methicillin resistant Staphylococcus aureus (MRSA). This research aimed to identified and understand the resistance of MRSA bacteria from Wagner grade I and II diabetic ulcers at department of Internal Medicine of RSUD Arifin Achmad. Samples were taken with a swab technique and then the bacteria were identified and further resistance test with Kirby-bauer disk diffusion method. This research reported about 6 samples (21,42%) from 28 grade I and II swabs diabetic ulcers are Staphylococcus aureus and 5 samples 83,33% from 6 samples Staphylococcus aureus were identified as MRSA. Antibiotics trimethoprim-sulfamethoxazole, chloramphenicol and gentamycin resistance test results had sensitivity 100% to MRSA bacteria. Followed by ofloxacin 60% and ciprofloxacin 40%.Key words : Diabetes Mellitus, Diabetic ulcers, Methicillin resistant Staphylococcus aureus, Resistance